Cognitive and affective functions associated with insomnia: a population-based study. (3rd April 2017) - Hishikawa, Nozomi; Fukui, Yusuke; Sato, Kota; Ohta, Yasuyuki; Yamashita, Toru; Abe, Koji
Abstract: Objectives : The number of patients with insomnia is rapidly increasing as society ages. The influence of insomnia on cognitive, affective, and activities of daily living (ADL) functions has not been fully studied. Methods : Participants were 142 residents of a local super-aged community who underwent health check-ups provided by the local government. Participants completed cognitive, affective and ADL function tests including the MMSE. We divided participants into two subgroups based on Athens Insomnia Scale (AIS) scores (AIS ≤3 and AIS ≥4) and compared cognitive, affective, and ADL functions by sex and age. Results : Subjective insomnia (AIS ≥4) was found in 36.2% of participants and was more frequent in females than males. No differences were found in cognitive function between the AIS subgroups. For both sexes, Geriatric Depression Scale scores were significantly higher in the AIS ≥4 subgroup than the AIS ≤3 subgroup. Apathy Scale scores were significantly higher in males in the AIS ≥4 subgroup. Of the AIS subscales, 'sleepiness during the day' was significantly higher in females than males (** p < 0.01), especially in those aged ≥75 years (** p < 0.01). This group of older females also showed a significantly lower Trail Making Test scores (* p < 0.05). Discussion : Insomnia was present in 36.2% of the population in a Japanese super-aged community. Those with insomnia showed more depressive symptoms (both sexes) and males showed more apathy. The most distinct characteristic of females aged ≥75 years was a high frequency of daytime sleepiness, possibly related to a decline in attention and executive function.